2019
DOI: 10.31234/osf.io/azdu7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Smiles of Affiliation and Dominance when competing for Leadership: The effect of gender in the 2016 US Presidential Debates

Abstract: For human observers’ slight differences in the muscular configurations of the smile can communicate dominance or affiliation. Despite the significant role played by smiles, our gender modulates their valance. Females tend to smile more than men and are judged more negatively if they smile less than their male counterparts. Given that the smile is associated with effective leadership it remains to be seen whether or not gender moderates such displays during leadership campaigns. To examine this question the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Research shows that compared to males, females are more emotionally expressive and exhibit a higher facial responsivity to others’ emotion expressions [ 69 ]. Furthermore, recent studies have shown that female politicians display more intense and affiliative type of smiles compared to their male counterparts and are judged more negatively if they do not [ 70 ]. The existing body of EMG research predominantly focuses on emotion expressions of male politicians and does not extensively examine facial reactions of both male and female supporters/opponents (except for [ 2 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that compared to males, females are more emotionally expressive and exhibit a higher facial responsivity to others’ emotion expressions [ 69 ]. Furthermore, recent studies have shown that female politicians display more intense and affiliative type of smiles compared to their male counterparts and are judged more negatively if they do not [ 70 ]. The existing body of EMG research predominantly focuses on emotion expressions of male politicians and does not extensively examine facial reactions of both male and female supporters/opponents (except for [ 2 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our sample was predominantly female with target politicians examined being all male, hence we were unable to examine gender related effects. Recent studies have shown that female politicians tendentially display more intense and affiliative type of smiles compared to their male counterparts and are judged more negatively if they don't (Senior et al, 2019). More studies are needed to examine the modulation effect of gender in whether and how politicians' smiles are perceived and facially responded to.…”
Section: Discussionmentioning
confidence: 99%
“…However, smiling can be a social act, especially when interacting with others (LaFrance 2011; LaFrance and Hecht 2011). This has been clear on the campaign trail, as Hillary Clinton performed far more intense smile displays than Donald Trump during the 2016 presidential debates, and Representative Madeleine Dean reported having an aide hold a sign during campaign events to remind her to smile (Astor 2019;Senior, Ridout, and Stewart 2019).…”
Section: Gender Stereotypesmentioning
confidence: 99%